Between Logic of Blessing and Accounting Rationality: Financial Reporting Formalization Process in a Sharia Property Developer - Icha Mustamin; Alimuddin; Darwis Said (Poltanesa, 2025)
This research explores the meaning of accountability and the fundamental challenges arising during the transition from a manual reporting system to a formal accounting system in a non-bank Islamic property developer. Utilizing a qualitative approach with an in-depth design, the researcher served as a participant-observer for over five months at PT. Pandawa Lima Development in South Sulawesi. Data collection involved triangulation of semi-structured interviews, participant observations, and document analysis to ensure validity. The findings identify the existence of a "logic of blessing" as the dominant rationality replacing conventional market logic, manifested in the owner's migration story and the company's ability to survive three years without sales, interpreted as divine help. The formalization challenge was not merely technical but an intensive sense-making process to translate intuition-based practices into an inflexible account code structure. The study highlights that accounting formalization in this context is a negotiation between spiritual values and technical rigidity. This research contributes to the literature by providing bottom-up empirical data on accounting practices in non-banking Islamic entities and offers practical insights for integrating spiritual values into formal reporting systems without eroding the organization's unique ethos.